Studi Eksperimental Pengaruh Jarak Tempuh Dan Temperatur Udara Sekitar Terhadap Penurunan Nilai Viskositas Oli Mesin Pada Engine 125 CC - Amnur Akhyan; Roy Sahata (Jurnal Teknik Mesin, 2024)
There are various types of motorbike oil, riders can choose oil according to their needs. This experiment aims to find out which oil is suitable for use by a 125 cc engine at different air temperatures according to the driver's needs. This experiment will analyze the reduction in oil viscosity values ​​with brands of oil A, oil B and oil C. The mileage used is 20 km, 40 km and 60 km with air temperatures of 33-36°C and 28-30°C. The viscosity value was measured using a Brookfield viscometer. Based on the results of the tested data, the percentage reduction in viscosity value at an air temperature of 33-36°C with a distance of 60 km is Oil A 26%, Oil B 62%, and Oil C 19%, therefore Oil C is better used in areas with a temperature of 33-36°C because it does not experience a significant decrease in viscosity. The percentage reduction in viscosity value at an air temperature of 28-30°C with a distance of 60 km is oil A 11%, oil B 62%, and oil C 62%, so oil A is better used in areas with a temperature of 28-30°C.